Elimination of the consequences of armed aggression in Ukraine: application of modern technologies in the inspection of damaged buildings and structures - Shatrova, I.; Demydova, O.; Malonkina, I. (Ways to Improve Construction Efficiency, 2024)
This study aims to consider the improvement of technical inspection methods in the context of military conflict. Taking into account the factor of human safety in the survey process, the search for optimal methods and technologies for data collection and analysis is carried out, in particular, the use of modern technologies such as unmanned aerial vehicles (UAVs) and geographic information systems (GIS) is considered. The use of drones allows for quick and efficient surveys of hard-to-reach areas and the collection of high-quality damage data. The integration of UAVs with GIS provides a systematic view of large-scale destruction problems and helps to make informed decisions on how to address the consequences of armed aggression. Despite the advantages of using these technologies, their limitations should be taken into account. The combination of different survey methods allows to obtain the most complete and accurate information about the condition of buildings and structures, which is key in making decisions on the restoration and reconstruction of the affected areas. The study examined the practical use of these technologies within the framework of the Rebuild ua project, which digitized the main destructions in Chernihiv, Sumy, and Kyiv regions. The use of unmanned aerial vehicles in combination with geographic information technologies allows to systematize, analyze, obtain visual information and images with geometric data, which simplifies the process of damage assessment and decision-making during the survey procedure. GIS technologies are also capable of analyzing geographic data, visualizing damage on a map, locating damaged objects and assessing their damage. The integration of GIS technologies and unmanned aerial vehicles with other systems makes it possible to simplify decision-making on the priorities of liquidation and recovery.